Assessment of patient expectations toward health professionals and quality of life among Płock (Poland) residents aged 55 and over: a cohort study - Głowacka, Mariola; Gasik, Monika; Kujawa, Waldemar; Cybulski, Mateusz; Pluta, Agnieszka (Frontiers in Public Health, 2024)
BackgroundThe right attitude of health professionals (mainly doctors) towards patients—particularly older ones—determines patients’ level of illness acceptance and quality of life. The aim of the study was to assess patient expectations of health professionals and quality of life among residents of Płock (Poland) aged 55 and over in relation to sociodemographic variables and to examine correlations between these patients’ expectations and their quality of life.MethodsThe study included 2040 adults aged 55 and over, with 68.9% being women. A diagnostic survey was used, incorporating sociodemographic questions and two standardized scales: the Patient Request Form (PRF) and the 36-Item Short Form Health Survey (SF-36). This cohort study utilized a multi-stage sampling method, with data collected through a diagnostic survey. Data analysis incorporated ANOVA, post-hoc Fisher’s LSD tests, and Pearson’s correlation to assess relationships between variables.ResultsStatistically significant differences were observed between male and female respondents in their expectations of health professionals. Women reported higher scores than men across all three PRF scales, including emotional support (4.85 vs. 4.35, p < 0.05), test- and treatment-related information (7.41 vs. 6.81, p < 0.05), and explanation of the illness (6.89 vs. 6.47). A low but statistically significant correlation was found between age and expectations for emotional support (r = 0.162, p < 0.001), as well as test- and treatment-related information (r = 0.122, p < 0.001). Respondents with secondary/post-secondary education reported the highest expectations for explanation of the illness (mean = 7.06) and test- and treatment-related information (mean = 7.64). Meanwhile, respondents with lower education levels, especially those with primary or vocational education, reported the highest expectations for emotional support (mean = 4.93). The average QoL score measured by the SF-36 was 63.45 (SD = 17.68), indicating moderate-to-high overall QoL. The mental component summary score (mean = 65.07, SD = 19.69) was slightly higher than the physical component summary score (mean = 62.70, SD = 18.06). Age was negatively correlated with QoL scores, particularly in the physical component (r = −0.407, p < 0.001). Education level positively influenced QoL, with respondents holding tertiary education reporting the highest QoL scores.ConclusionWhat the older adults included in our study expect most from health professionals is full and ac-curate medical information, particularly information about their health. Overall, the respondents reported moderate, bordering on high, quality of life. The quality of life of the respondents and their expectations of health professionals were influenced by sociodemographic characteristics, and in particular sex, age and education level.